Interleukin-10 Induces Expression of Neuroendocrine Markers and PDL1 in Prostate Cancer Cells - Abrar Samiea; Jeff S. J. Yoon; Christopher J. Ong; Amina Zoubeidi; Thomas C. Chamberlain; Alice L.-F. Mui (Prostate Cancer)
Interleukin-10 (IL10) is best studied for its inhibitory action on immune cells and ability to suppress an antitumour immune response. But IL10 also exerts direct effects on nonimmune cells such as prostate cancer epithelial cells. Elevated serum levels of IL10 observed in prostate and other cancer patients are associated with poor prognosis. After first-line androgen-deprivation therapy, prostate cancer patients are treated with androgen receptor antagonists such as enzalutamide to inhibit androgen-dependent prostate cancer cell growth. However, development of resistance inevitably occurs and this is associated with tumour differentiation to more aggressive forms such as a neuroendocrine phenotype characterized by expression of neuron specific enolase and synaptophysin. We found that treatment of prostate cancer cell lines in vitro with IL10 or enzalutamide induced markers of neuroendocrine differentiation and inhibited androgen receptor reporter activity. Both also upregulated the levels of PDL1, which could promote tumour survival in vivo through its interaction with the immune cell inhibitory receptor PD1 to suppress antitumour immunity. These findings suggest that IL10’s direct action on prostate cancer cells could contribute to prostate cancer progression independent of IL10’s suppression of host immune cells.